Medicine in Balkans during the Roman Period - Daniş Baykan (Balkan Medical Journal, 2017)
The aim of this study is to investigate the archaeological finds to enlighten the medical methods of treatments and operations applied in Balkans during Roman Period. Some independent local and regional find groups, taken from existing publications will be grouped together and a holistic point-of-view will be taken against medicine in Balkan Geography during Roman Period. Due to basic differences it contained, the data before Roman Period are excluded. Most of Greece and Aegean Islands are also excluded since the topic selected is “Medicine of Roman Period.” Greece and Aegean Islands should be evaluated in another study in connection with West Anatolia which is closer than the Balkan Geography in terms of social relations. The spread of medical tools in Balkans during Roman Period is concentrated around military garrisons, and in settlements built around military pathways, and in settlements containing an amphitheater associated with gladiators. This spread is verified by the studies on Bulgaria in general. The data is also compatible with the assertion suggesting that the amount of application of pharmaceutical treatment increases when one moves away from the military centres